Implementation of Inclusive Education Policy - Ekawati, Diyan; Lian, Bukman; Mahasir, Mahasir (Yayasan Sembilan Pemuda Indonesia, 2023)
This study aims to analyze the implementation of the inclusion education policy at the Regional Technical Implementation Unit SD Negeri 4 Koba, analyze the supporting and inhibiting factors for the implementation of inclusion education at the Regional Technical Implementation Unit SD Negeri 4 Koba Education Unit and provide recommendations for solutions for the development of inclusion education at the Regional Technical Implementation Unit SD Negeri 4 Koba Education Unit. This study used a qualitative approach, with observation, interview and documentation methods. The respondents in this study consisted of school principals, teachers and education staff, parents, heads of the Central Bangka Regency Education Office, psychologists and Office of Population Control, Family Planning, Women's Empowerment and Child Protection. The results of the study concluded that the implementation of the inclusive education policy at the Regional Technical Implementation Unit Education Unit SD Negeri 4 Koba has been going well, but still needs some improvement and support from the local government.